What makes the difference between a low-cost carrier airport and a low-cost carrier base?. (December 2016) - Zuidberg, Joost; de Wit, Jaap
Abstract: The liberalization of the European air transport market has enabled airlines to expand their networks substantially throughout the continent. In particular, low-cost carriers (LCCs) did so by rapidly expanding their number of bases in countries all over Europe. This paper sheds light on the variables that are related to the base likelihood of Ryanair, easyJet and Wizz Air, using several logistic regression models on a rich dataset with 385 European airports. The analysis shows that population is positively related to base likelihood. This relation is substantially stronger for easyJet bases. In addition, Ryanair base likelihood is positively linked with the number of hotel beds near the airport. EasyJet bases do not show such a relationship. Ryanair and especially Wizz Air bases are located in less wealthy regions, while easyJet bases are located in slightly richer regions. In addition, an obvious positive relationship between base likelihood and the number of airport operating hours is shown. The level of labour costs is related negatively to base likelihood. Airport competition turns out not be related to base likelihood. Finally, Ryanair's bases are often only served by LCCs, while easyJet target airports that have a mixed airline portfolio.